Pengelolaan Estetika lingkungan RW 003 Asem Payung Kelurahan Gebang Putih Kecamatan Sukolilo - roosandriantini, josephine (Dharma: Jurnal Pengabdian Masyarakat, 2022)
Infrastructure development in Indonesia continues to increase from the village scale to the national and even international scale. There are so many areas that we usually refer to as "villages" that also need to be changed, developed, and managed to provide an increase in the aesthetic value of the environment. The village becomes the specialty of an area within an area, where the village with its uniqueness can be better known and admired by many people. The existence of Asem Payung village must have special characteristics to support the activities of residents in the neighborhood. This village is still very lacking in terms of environmental management, so it looks good in terms of aesthetics. The dividing wall is unsightly and looks shabby so it needs further improvement. The method used in this community service activity is a qualitative descriptive method. An environment that is not clean and looks shabby is the main problem in this environment. In addition, it is necessary to monitor and evaluate and assist the surrounding community in the concept of gotong-royong to improve the aesthetics of the environment and make it look even better. The expected result in the Asem Payung village area is to be better in the aesthetic appearance of the environment by being filled with mural paintings with educational themes. So that this area turns out to be a place for visits or tours to arrange a neat and clean environment far from the impression of slums.